La psi coeducación para mejorar los niveles de autoestima en los residentes del centro terapéutico salvando al adicto de la ciudad de Loja período junio-agosto 2016 - Morales Castillo, Ana Lizeth (2017)
Low self-esteem is the difficulty that the person to feel deep valuable in itself, and therefore worthy of being loved by others. People with low self-seeking, sometimes without being very aware of it, the approval and recognition of others and often have difficulty to be themselves and to express freely what they think, feel and need in their interpersonal relationships, becoming in an increasingly difficulty increases in society, hence the need to investigate. PSYCHOEDUCATION TO IMPROVE THE LEVELS OF SELF-ESTEEM IN THE RESIDENTS OF CENTER THERAPEUTIC SAVING ADDICTED CITY OF LOJA PERIOD JUNE-AUGUST 2016. The work was framed in action research, through the intervention of descriptive character, explanatory type of quantitative both qualitative approach, methods as scientific, analytical, inductive, descriptive was used, test instruments such as the self-assessment of Lucy Redil which will assess the levels of self-esteem and recording daily activities was applied. The population was 25 inmates at the treatment center "Saving Censadic Addict" sample selection was raised at the suggestion of determining Clinical Psychologist 17 cases, with whom worked psychoeducational activities; concluded that psychoeducation applied properly and consistently helps to improve self-esteem in a high percentage, so it is recommended to continue with those activities center to optimize recovery and strengthen a new lifestyle of local residents.